“Não toquem na minha igreja!”: um estudo de caso acerca da Revolução Tranquila no Québec - Rautmann, Robert (2021)
The object of this doctoral thesis is the Quiet Revolution, which took place in Québec, a province of Canada, in the 1960s and aims to analyze the circumstances of the removal, or reduction, of the participation of the Catholic Church in Québec society in that period. The theoretical framework is supported by concepts that intend to explain this process, in which sectors of society and culture were removed from the influence of religious institutions, such as: secularization, laicization, desacralization. The working hypothesis is that the movement of withdrawal of the Church, in relation to these spheres of society, started from within the Catholic Church, from theological movements, from pastoral practices, from internal criticism, which were in line with the historical contexts of the time, in which religious authority was already contested. Through a case study, which is a broad research method aimed at deepening a certain knowledge, the present work will deal with the Quiet Revolution, its antecedents and consequences. Québec is Canada's largest province, in terms of land area, as well as being the second most populous. Its population is mostly Francophone and Catholic, unlike the rest of the country. Its history, since its foundation, is linked to the development of the Catholic Church in North America. Amid the clashes between England and France, Québec preserved its French culture and language through Catholicism. The Catholic Church has been, for centuries, the central reference for Quebecers. In the 1960s, the Liberal Party rose to power and Jean Lésage became Prime Minister of Québec. His government was remarkable in the history of the Province and is linked to what is known as the Quiet Revolution. This period is known for a series of social, political and economic changes in the region, and considered to be the founding landmark of modern Québec. It was during this same period that the Catholic Church was removed from certain positions of management and authority in Québec society. As a case study, the work also presents elements of analysis that may provide opportunities for future considerations in relation to the different realities of this study. It is important to highlight that the theme is the object of numerous researches in Québec. In Brazil, however, it is little explored